A falta de cidadania e a inefetividade dos direitos fundamentais dos presos - Taufner, Domingos Augusto (2008)
The present work analyses the relationship between the absence of citizenhood in Brazil and the infectivity of the fundamental rights of the prisoners. As the research is developed, it is used the “dialectic” methodology, having, as a prime source, the bibliographic search of juridical works and other areas of knowledge, in a “transdisciplinar” perspective. It works with a wide concept of citizenhood, that doesn’t straiten itself to the civil and political rights, but embraces the social rights as well. It mentions the main historical basis of citizenhood, observing how its concept has evolved through the Brazilian Constitutions, leading to the current Constitution of 1988, which relates to the wide vision of the subject. It approaches the human rights, its dimensions, its contemporary challenges, its context in the current reality, as well as the need of effectivity. It describes the main fundamental rights of the prisoners and sued individuals in the Constitution of 1988, reflecting most strongly about the presumption of innocence, the prohibition of torture and cruel penalties, including the capital punishment. It researches the prejudice of society against prisoners, appealing to the social psychology to analyze the phenomenon. It alerts that the lack of effectivity of the Penal Execution Law in an overoccupied and inhuman penitentiary system makes it difficult to execute the human rights of the prisoners foreseen in the constitutional text. It emphasizes the importance of the complete access to justice, which does not limit itself to access to the courts, as an element of guaranty of the fundamental rights to the prisoners and sued individuals. It remarks that the execution of the social rights foreseen in the national law is a way to guarantee full citizenhood to people, because in order to access completely the civil and politic rights it’s necessary to have access to education, employment etc., but there are difficulties in the execution of these rights. It relates the absence of citizenhood (especially for the prejudice against prisoners, for the lack of access to justice, for the lack of effectivity of the Penal Execution Law and for the lack of effectivity of the social rights) as a cause of increase of criminality and, then, of the prison population, making it harder, with that, to effective the fundamental rights of the prisoners and sued individuals. It gets to the conclusion that the prison penalty is inevitable in the Brazilian context, but that it should be applied only when strictly necessary, and respecting the fundamental rights of the human person, which can only be guaranteed in a nation that respects citizenhood.